2020
DOI: 10.1371/journal.pone.0242172
|View full text |Cite
|
Sign up to set email alerts
|

Linking nighttime outdoor lighting attributes to pedestrians' feeling of safety: An interactive survey approach

Abstract: Public space lighting (PSL) contributes to pedestrians’ feeling of safety (FoS) in urban areas after natural dark. However, little is known how different PSL attributes, such as illuminance, light temperature, uniformity and glare, affect people's FoS in different contextual settings. The present study aims to bridge this knowledge gap by developing a model linking different PSL attributes with FoS, while controlling for individual, locational, environmental and temporal factors. To develop such model, the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
(45 reference statements)
1
13
0
Order By: Relevance
“…Light can affect human health [ 5 ], which can be both positive and negative [ 6 ]. Inappropriate ALAN can affect human emotions [ 7 , 8 ], perception, evaluation, behavior [ 9 , 10 ], and feeling of safety [ 11 ] and can even have a significant impact on physical health [ 5 , 6 , 12 14 ]. If humans are exposed to an uncomfortable light environment for a long time, such as insufficient brightness, uneven lighting, uncomfortable glare, and intense strobe light, it will not only cause serious harm to their physical health but also affect their psychological health [ 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Light can affect human health [ 5 ], which can be both positive and negative [ 6 ]. Inappropriate ALAN can affect human emotions [ 7 , 8 ], perception, evaluation, behavior [ 9 , 10 ], and feeling of safety [ 11 ] and can even have a significant impact on physical health [ 5 , 6 , 12 14 ]. If humans are exposed to an uncomfortable light environment for a long time, such as insufficient brightness, uneven lighting, uncomfortable glare, and intense strobe light, it will not only cause serious harm to their physical health but also affect their psychological health [ 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The factors influencing FoS after dark include not only illuminance, but also other lighting attributes, such as uniformity, light color rendering, and light color temperature [10]. Studies by Portnov et al [11], Saad et al [12], and Svechkina el al. [13] were based on a modern mobile phone survey technology for data collection, and indicated that illumination levels, either perceived or instrumentally measured, can affect the feeling of safety (FoS) of pedestrians after dark.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Svechkina et al [13] established an evaluation model between road lighting attributes and the feeling of safety (FoS), and found that lighting has a certain positive impact on FoS. In addition, Portnov et al [11] established a model linking different PSL attributes with FoS. The research shows that higher illumination level and uniformity have a positive impact on FoS, and rich blue light has a negative impact on FoS This conclusion is supported by another recent study by Saad et al [12], who found that using warmer lights and increasing light uniformity can help to save energy while maintaining a reasonable FoS level.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, on the one hand, taking advantages of the high sense of presence experienced in immersive virtual reality environments means that Virtual Reality will increasingly become the tool that designers and administrators will use to select alternatives, not exclusively based on the target values of the lighting metrics indicated in international standards, but by a human-centric and participative approach, as well as on expectations, preferences, satisfaction and feeling of citizens. This will help them consider peculiarities and sensibilities of local communities toward several lighting related aspects having direct or indirect consequences on citizens' behavior (accessibility, safety) [31,52,53] and health (biological functions and rhythms) [9,54], tourists (landmarks, lighting gates) [55,56], animals and vegetation (attraction, reproduction) [6,8,9], as well as light pollution [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence links circadian disruption to major depression and other mood disorders [30]. Regarding the sense of safety, lighting is one of the most important aspects affecting public spaces' perceived quality and attractiveness [31,32]. The sense of security in urban parks is mainly related to visibility [33].…”
Section: Introductionmentioning
confidence: 99%